(untitled) - Bradley D Brown (Berkeley, California, 1998)
The book includes undocumented strategies for designing, building, implementing, and supporting Web applications. Sample scripts, taken from real-life examples. It also shows how to build effective applications in an Oracle RDBMS environment
Keywords: client/server computing,computer networks,network computer,web